21 Realist Review of General Practitioners' Role in Advancing Practice in Care Homes (Grape Study). (16th March 2021) - Chadborn, N H; Gordon, A L; Devi, R; Williams, C; Goodman, C; Sartain, K
Abstract: Introduction: Many care home residents have high levels of complex needs and their medical care is the responsibility of the general practitioner (GP) in UK. GPs have multiple roles, including gatekeeper for access to other healthcare services and often play a leadership role in the healthcare team. Our aim is to develop realist programme theories for how GPs interact with care homes to facilitate improvements in care of residents. Method: Using realist review we aimed to describe "what works" for GPs to be involved in improvements in care of residents. Firstly we carried out a scoping review of UK literature and interviewed GP leaders in order to build programme theory. Secondly iterative literature searches were performed in Medline, Embase, CINAHL, PsycInfo, ASSIA, Scopus and many grey literature databases. This international literature is being used to test and refine programme theories and to explore the range of contexts. Results: A scoping search identified a small number (n = 5) of recent UK articles (2010–19) that described GP input into quality improvement. To gain insight into context, observational studies (n = 4 in UK and Ireland) were identified which described concerns about workload and resource constraints. To develop initial programme theories, we conducted interviews with 6 GP leaders, where themes of risk and specialism were identified. We are developing the following mechanisms within programme theory: where GP profession have an ownership of the agenda, this encourages GP involvement. In other initiatives, the mechanism may be a trusting relationship between GP and another practitioner, eg pharmacist. Conclusion: Many reported projects which aim to improve care quality in care homes do not describe how the initiative relates to GP practice. We have identified mechanisms which, when present, may cause GPs to contribute leadership and medical expertise, and thus lead to successful outcomes for residents.